Study of the structure of titanium thin films deposited with a vacuum arc as a function of the thickness - Fazio, Mariana Andrea (2015)
Polycrystalline titanium thin films have been widely employed as interlayer between the substrate and different coatings in order to improve adhesion strength, corrosion resistance and wear performance, as well as to promote the growth of crystalline phases of the coating. The thickness of the Ti layer can be relevant on the behavior of the coatings, however very few studies have been carried out. In this work, the crystal structure of polycrystalline titanium films deposited with a vacuum arc discharge on monocrystalline silicon wafers (100) was studied and a dependence on the film thickness was found. The presence of the fcc phase of titanium was observed for the thinnest films with a critical thickness estimated in 300 nm, a much larger value than those reported for other deposition processes. For larger thicknesses, the films grew as α-titanium with a preferred orientation in the [100] direction. The obtained results agreed with a growth model based on the matching between the film and the substrate lattice. The characteristics of the films deposited in two steps, which had not been previously investigated, reinforced the suggested model.